Про світ-системний підхід до дослідження економіки промисловості - Cherevatskyi, Danilo Yu. (Institute of Industrial Economics of NAS of Ukraine, 2019)
Against the background of current discussions on the conceptual framework of institutional researches, the topic on the necessity of significant changes in the approach itself is becoming increasingly relevant. In this regard, it may be useful to refer to the world-system analysis, but accustomed to the industrial economics. As in the case of the world-system analysis, which implies that national states are not societies with separate, parallel histories, but represent parts of a whole, reflecting this whole, it is also appropriate to consider elements of the microeconomics in their economic and historical interaction and interdependence in the framework of industrial economics.Due to the abovementioned, the objective of the paper is to summarize the development of business structures of industrial economics in the light of the world-system analysis’ ideas.To achieve this goal, next tools and methods were used: microcosm-system analysis.Results and conclusions. The analysis of the historical development of business structures in the international coal industry and the coal engineering sector as mini-systems, microcosm-economies and microcosm-empires is carried out. The effects of interaction between coal mining structures and enterprises, supplying equipment to them in countries with unprofitable and cost-effective coal mining, are shown. The tendency of multinational microcosm-empires’ expansion and the spread of alliances of microcosm-economies (microcosm-empires) were revealed.